Fat girl a true story - Moore, Judith (Hudson Street Press, 2005)
A memoir of one woman's obsession with food sets the author's love/hate relationship with food against her painful longing for a family, love, and a sense of belonging.
Keywords: Moore, Judith -- 1940-; Overweight women -- Biography; Biografie